The Effect of Photo-Initiated Oxidation on Mechanical Properties of High Density Polyethylene / Linear Low Density Polyethylene Blends - J. Saleh, Najat; A. Mohammed, Nabeela (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The long – term behaviour of polyethylene products used out doors is affected by weathering. In the present work, weathering test was carried out to find the effect of the environment conditions on the mechanical properties of HDPE/LLDPE blends with different weight percents (0, 15, 30, and 45 %) relative to the LLDPE by increasing the exposure times to (100, 150, 200, 250, 300) hr. A series of tests (destructive), tensile, impact and hardness were carried out on the prepared samples, the results obtained declare the changes on the material behaviour from ductile to brittle and the polymer shows a decline in the mechanical properties with increasing the exposure times. In the present work empirical equations were reached which could be used to calculate one of the mechanical properties in terms of exposure time, weight percent of LLDPE content and to other mechanical properties.